Beyond BMI: the complex interplay of reward sensitivity, eating behaviors, and BMI in female college students - Aldhwayan, Madhawi; Alabdulkader, Shahd; Miras, Alexander Dimitri; Alhusan, Shadeena; Alghmdi, Khloud; Albarqi, Hanan; Almousa, Zainab; Alshaalan, Rasha (Frontiers in Psychology, 2025)
BackgroundHeightened reward sensitivity (RS) may lead to greater preference for high-calorie foods, excessive intake, and weight gain. However, the association between RS, eating behavior traits, and body mass index (BMI) remains unclear.ObjectiveWe examined the relationship between RS and BMI and explored the associations of eating behavior traits with RS among female college students.MethodsA cross-sectional study was conducted with female students aged 18–25 years in Riyadh, Saudi Arabia. Anthropometric measurements were obtained to calculate BMI. Eating behaviors were assessed using the Three-Factor Eating Questionnaire, which measures cognitive restraint, disinhibition, and hunger. RS was evaluated using the progressive ratio task. Correlations between BMI, RS, and eating behavior traits were analyzed using non-parametric statistical methods.ResultsThe data of 89 students were analyzed. No significant associations were found between BMI and RS. Similarly, there were no significant correlations between RS and any of the eating behavior traits. Among the Three-Factor Eating Questionnaire subscales, only disinhibition was significantly positively correlated with BMI (r = 0.21, p < 0.05). RS (breakpoint) was positively correlated with hunger (r = 0.25, p < 0.05) and negatively correlated with cognitive restraint (r = −0.40, p < 0.001). There were no significant differences in breakpoint scores between participants with low and high BMI.ConclusionAlthough no significant associations were observed between BMI and RS or between RS and eating behavior traits, the findings contribute to understanding the complex interplay between psychological and behavioral factors in eating and weight regulation.